2015
DOI: 10.1159/000365223
|View full text |Cite
|
Sign up to set email alerts
|

Globus Pallidus Internus Deep Brain Stimulation as Rescue Therapy for Refractory Dyskinesias following Effective Subthalamic Nucleus Stimulation

Abstract: Background: Deep brain stimulation (DBS) at the subthalamic nucleus (STN) or globus pallidus internus (GPi) can effectively treat the motor symptoms of Parkinson's disease, but dual implantation is rare. We report the first cases of additional GPi stimulation as rescue therapy for disabling dyskinesias following successful STN stimulation. Methods: Two patients, initially treated with bilateral STN DBS, underwent subsequent bilateral GPi DBS after the development of refractory dyskinesias within 1 and 6 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…In certain patients, up titration of dopaminergics in attempts to adequately control breakthrough symptoms can also lead to disabling side effects (neuropsychiatric changes, fatigue, sleep disruption, impulse control disorders, orthostatic hypotension, and dyskinesia among others). Case studies and series have reported using additional leads in the other primary PD DBS target (i.e., STN stimulation to rescue failed GPi stimulation and vice versa) in these circumstances with some success [15,26,27,28,29,30]. …”
Section: Parkinson’s Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…In certain patients, up titration of dopaminergics in attempts to adequately control breakthrough symptoms can also lead to disabling side effects (neuropsychiatric changes, fatigue, sleep disruption, impulse control disorders, orthostatic hypotension, and dyskinesia among others). Case studies and series have reported using additional leads in the other primary PD DBS target (i.e., STN stimulation to rescue failed GPi stimulation and vice versa) in these circumstances with some success [15,26,27,28,29,30]. …”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Published cases where patients underwent GPi stimulation for failed STN stimulation generally report patients with a young age of disease onset (average age 41) and a long interval of success with their initial STN surgery (average of 8 years until rescue surgery) [26,27,29,30]. In all reviewed cases, the reason for failure was disabling dyskinesia or dystonia.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
See 3 more Smart Citations